The News Sharing Gap - Diógenes Lycarião; Marcelo Alves dos Santos; Ana Beatriz Leite (Brazilian Journalism Research, 2021)
ABSTRACT – Current literature on online news sharing presents a range of methods and results, alongside contradictory explanations for the phenomenon. To disentangle this, we compared three countries with contrasting levels of political stability (Brazil, Canada and the US). A content analysis of articles (n = 1.658) posted in 2016, on the main news pages in Facebook for each country, shows that the Canadian news pages presented far less news sharing on national politics conflicts than Brazil and the US did. We discuss how this shows the relevance of political context in explaining both news routines and shareworthiness.